Characterization of the enzymatic resistance to β-lactamics in enterobacteria - Castillo, Natalia Alejandra (2007)
Detecting the resistance to CTG in severe infections-by enterobacteria guides to successful treatments. The main resistance mechanisms are the production of extended spectrum β-lactamases (BLEE), chromosomal inducible or derepressed β-lactamases Amp-C type or plasmidic Amp-C. The aim of this study was to investigate and characterize the mechanisms involved in the resistance to CTG in clinical isolations of enterobacteria, by phenotypic and genotypic methods. 64 isolations resistant to CTG were studied (K. pneumoniae, E. coli, Enterobacter spp and Proteus spp ). Antimicrobial agents sensibility and phenotypic detection of Amp-C and BLEE enzymes was performed by diffusion and dilution methods. In cefotaxime resistant E. coli and K. pneumoniae strains a possible enzymatic resistance mechanism was detected by Masuda Bioassay. The genes bla CTX-M-2 and bla PER-2 were detected by PCR. Of 64 isolations, 8 strains were presumptively producers of derepressed Amp-C and 56 were BLEE producers (with prevalence of CTX-M-2). Accompanying resistance was observed. Masuda Bioassay was negative and accompanying resistance suggests it is due an impermeability phenomenon. Our results confirm that the resistance to CTG in our strains is mainly caused by enzymes coded in plasmids so that it merit to establish epidemic control measures and to emphasize wise use of β-lactamic agents available.